1988
DOI: 10.3102/00346543058004438
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Classroom Evaluation Practices on Students

Abstract: In most educational programs, a substantial proportion of teacher and student time is devoted to activities which involve (or lead directly to) evaluation by the teacher of student products or behavior. This review summarizes results from 14 specific fields of research that cast light on the relationships between classroom evaluation practices and student outcomes. Particular attention is given to outcomes involving learning strategies, motivation, and achievement. Where possible, mechanisms are suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
405
1
43

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 903 publications
(462 citation statements)
references
References 153 publications
13
405
1
43
Order By: Relevance
“…This lack of convergence on assessment is disconcerting. Assessment is integral to the quality of learning outcomes and critical to student learning and retention (Biggs and Tang 2011, Morgan et al 2007, Crooks 1988. One explanation for the lower academic perceptions is that academics experience a smaller sample of assessment tasks than students.…”
Section: Programmatic Assessment Framework For Graduate Learning Outmentioning
confidence: 99%
“…This lack of convergence on assessment is disconcerting. Assessment is integral to the quality of learning outcomes and critical to student learning and retention (Biggs and Tang 2011, Morgan et al 2007, Crooks 1988. One explanation for the lower academic perceptions is that academics experience a smaller sample of assessment tasks than students.…”
Section: Programmatic Assessment Framework For Graduate Learning Outmentioning
confidence: 99%
“…This finding suggests that students in classrooms where teachers adopted a constructivist conception of learning had a negative level of test anxiety, whereas students in classrooms where teachers adopted the traditional one had a positive level of test anxiety. Hence, this finding informs that students have lower level of test anxiety in constructivist classrooms, so that measurement and evaluation methods out of formal tests and examinations are very important, resulting in low level of test anxiety in students (Crooks, 1988). Therefore, it may be suggested that students should be educated in classrooms where teachers adopt constructivist teaching-learning conception (e.g., Alsup, 2004;Baş, 2015b).…”
Section: Implications For Practicementioning
confidence: 99%
“…Moreover, it gives the student the opportunity to practise skills and consolidate learning. Feedback allows the student to monitor their progress and develop selfevaluation and critical thinking (Crooks, 1988;Gibbs and Simpson, 2005). The effects of formative assessment in promoting self-regulated learning are well known (Nicol and Macfarlane-Dick, 2006).…”
Section: Introductionmentioning
confidence: 99%